A TNNI2 variant c.525G>T causes distal arthrogryposis in a Chinese family. Issue 12 (7th September 2022) - Li, Yue; Nong, Tianying; Li, Yiqiang; Li, Xia; Li, Zhaohui; Lv, Hui; Xu, Hongwen; Li, Jingchun; Zhu, Mingwei
Abstract: Background: Distal arthrogryposis (DA) is a group of congenital autosomal‐dominant disorders secondary to defects in joint and muscle function, characterized by multiple joint contractures of the hands and feet. DA can be divided into 10 types according to clinical features. DA has been confirmed to be caused by mutations in genes encoding components of the contractile apparatus of skeletal muscle fibers, such as troponin I2 ( TNNI2 ). Methods: In this study, we report a three‐generation DA family belonging to the DA2B type. The clinical characteristics of affected members are genetically stable and consistent, with severe deformities in hands and feet, and two affected adults had short stature. None exhibited facial abnormalities. Blood from three affected and three healthy members were collected for whole‐exome sequencing and Sanger sequencing. Results: A missense variant in TNNI2 (NM_003282.4: c.525G>T: p.K175N) was successfully identified, which resulted in the substitution of amino acid at position 175 of TNNI2 from lysine to asparagines. Conclusion: The variant c.525G>T in TNNI2 explains the cause of DA in the family. This variant was identified in Chinese people for the first time, and the same variant had been reported in another study but no description of clinical symptoms. Our study comprehensively characterized the c.525G>T variant in TNNI2 . Abstract : A three‐generation Chinese family with Distal arthrogryposis type 2B show short stature and severe deformity of the hands and feet, but without the typical facial abnormality phenotype of DA2B. We identified a missense variant in TNNI2 c.525G>T(p.K175N) in this family.